"And then, nothing": Alzheimer's archives and the good (enough) death. Issue 5 (28th May 2018) - Venema, Kathleen
ABSTRACT: This paper focuses on the author's mother, a subject whose ageing process was speeded and whose morality was challenged by the myriad and unpredictable effects of Alzheimer's disease. Using an archive of recorded conversations, the paper examines some of the existential questions with which the mother grappled until she lost the ability to speak. It considers these late ethical expressions in the context of her earlier political activism, marks her brief obsession with the possibility of assisted dying, and concludes by assessing the relative "goodness" of her very recent death in some of the terms that she herself established.